2014
DOI: 10.1002/macp.201400444
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Microphase Separation of PS‐b‐P(MA‐alt‐St) Block Copolymers and Their Ionomers for the Design of Polymer Crystallization Nucleation Agents

Abstract: Several well-controlled polystyrene-block -poly(styrene-alt -maleic anhydride) (PS-b -P(St-alt -MA)) functionalized block copolymers (BCs) and their sodium salt ionomers with different block ratios and molecular weights are synthesized through two-step reversible additionfragmentation chain transfer (RAFT) polymerization. The atomic force microscopy (AFM) images and differential scanning calorimetry (DSC) results reveal that the prepared BCs and their ionomers microphase separate into various nanostructures de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The T 0 m ( Table 2) was determined according to linear Hoffman-Weeks plot, which is important factor to investigate crystallization kinetics with Hoffman-Lauritzen secondary nucleation theory. In our previous work, the s e value of PET and PET/Surlyn has been calculated, which is 110.6 mJ m À2 and 47.1 mJ m À2 , respectively, indicating that the Surlyn reduce the s e of PET during the crystallization process [15]. Compared with PET and PET/OMMT, the s e values of PET/Surlyn, PET/SMA-Na and PET/IM were obviously decreased due to incorporating of ionomers as nucleating agents, indicating that ionomers are effective nucleating agents for PET, which was consistent with the results of non-isothermal crystallization.…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The T 0 m ( Table 2) was determined according to linear Hoffman-Weeks plot, which is important factor to investigate crystallization kinetics with Hoffman-Lauritzen secondary nucleation theory. In our previous work, the s e value of PET and PET/Surlyn has been calculated, which is 110.6 mJ m À2 and 47.1 mJ m À2 , respectively, indicating that the Surlyn reduce the s e of PET during the crystallization process [15]. Compared with PET and PET/OMMT, the s e values of PET/Surlyn, PET/SMA-Na and PET/IM were obviously decreased due to incorporating of ionomers as nucleating agents, indicating that ionomers are effective nucleating agents for PET, which was consistent with the results of non-isothermal crystallization.…”
Section: Samplesmentioning
confidence: 99%
“…Our recent work revealed that poly(styrene-alt-maleic anhydride) (SMA) ionomers (SMA-Na, Fig. 1d) can act as nucleating agent to improve the crystallization behaviors of PET [14,15]. However, the ionomers as nucleating agents cannot provide more and larger interfaces for crystal growth compared with that of inorganic compounds.…”
mentioning
confidence: 94%
“…On the other hand, the viscosity of PET will drop rapidly above melting temperature, leading to quite low melt strength and difficulties in the processing of foaming, blowing, thermoforming, etc. [9][10][11][12] To make up for these shortcomings, a large number of fillers such as inorganic nanoparticles, 13,14 organic metal salt 15 and ionomers [16][17][18][19] have been incorporated in PET to advance its mechanical properties. However, this strategy only has a weak influence on enhancing the performance of PET by improving crystallization property.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of alternating and block copolymers may open interesting perspectives for mimicking natural macromolecules. To date, by using two‐step or multi‐step method in the presence of free radical and ionic initiator, a few alternating copolymer‐ b ‐polymer such as polystyrene‐ b ‐poly(styrene‐ alt ‐maleic anhydride), [5] poly(ethyl vinyl ether)‐ b ‐poly(chlorotrifluoroethylene‐ alt ‐ethyl vinyl ether), [6] poly(maleic anhydride‐ alt ‐stearyl methacrylate)‐ b ‐poly(stearyl methacrylate), [7] poly(D,L‐lactic acid‐ alt ‐glycolic acid)‐ b ‐poly(L‐lactic acid) [8] etc. were reported previously.…”
Section: Introductionmentioning
confidence: 99%